The concept of imaginary homeland in the works of Indo-Caribbean writers - Mani, Manimangai (Bodhi International Journal of Research in Humanities, Arts and Science apr, 2018)
The concept of imaginary homeland is often found in the works of postcolonial writers. This term is derived from Salman Rushdie’s collection of essays titled Imaginary Homelands (2010). Imaginary Homeland is often found in the settings of the novels produced by immigrant writers. This paper intends to highlight the use of imaginary homeland in the settings in the works of selected Indo-Caribbean writers who originate from the islands of Trinidad and Tobago. The writers that will be discussed are V. S. Naipaul, Lakshmi Persaud and Shani Mootoo. These three writers are descendants of immigrants who moved to Trinidad during the colonization of Britain. The selected novels will be studied under the light of postcolonial theory to point the effects of migration on the immigrants. This paper will further highlight how these writers use imaginary settings to vent out their dissatisfaction upon their status as immigrants. These imaginary settings give them the liberty to create characters to act as their inner voice and finally these imaginary settings actually reveal their longingness for their motherland.